Pengaruh Persepsi Terhadap Perilaku Pembelian Blackberry Dan Implikasinya Pada Loyalitas Konsumen Studi Kasus pada Mahasiswa Sekolah Tinggi Ilmu Ekonomi Kesatuan - Mubarak, Mumuh Mulyana; Tandri, Riawati (Jurnal Ilmiah Ranggagading (JIR), 2012)
Perception is a good basis for consumers in finding the required product information. Perception will affect consumer buying behavior for the desired a needs product so expected the resulting product can make satisfied consumer and to be loyal. Consumer loyalty is very important for the company in maintaining the viability of companies and business success. The main objective of this study was to determine how much influence the perception of the buying behavior of the Blackberry and its implications on consumer loyalty. The used variables in this study is the independent variable is the perception consisting of brand, price, product and advertising. While the dependent variables is purchasing behavior and consumer loyalty. The analysis method is the Smart Partial Least Square (PLS) with deployment of 100 respondents questionnaire in area Sekolah Tinggi Ilmu Ekonomi Kesatuan Bogor. The research result showed that perception influential significant to buying behavior, where the significant result with t-statistics is 5.679652 and also perceptions influential significant to consumer loyalty, the significant results with T-Statistics is 4.063912. For while buying behavior also significantly to consumer loyalty where the significant result is 0.697294.